The Role of e-Trust and e-Service Quality on e-Loyalty of e-banking Consumers in Tangerang - Adi Widodo; Firdaus Putra; Sukriyah Sukriyah; Multi Nadeak; Dewiana Novitasari (Universitas Negeri Makassar, 2022)
The purpose of this study is to analyze the relationship of e-Trust to e-Loyalty, the relationship of e-Service Quality to e-Loyalty and the relationship of e-trust to e-Service Quality. The research method used in this research is quantitative research and explanatory survey. The data used in this study is primary data obtained by distributing online questionnaires to 566 bank customers who use the e-Banking application. The number of respondents was 566 respondents who were selected by simple random sampling of e-Banking application users in Tangerang. To analyze the data from the measurement results of the independent and dependent variables through an online questionnaire. The statistical data processing tool used in this research is SmartPLS 3.0. Based on data analysis, it can be concluded that e-Trust has a positive and significant effect on e-Loyalty, e-Service Quality has a positive and significant effect on e-Loyalty, e-Trust has a positive and significant effect on e-Service Quality.